Positive electrode slurry and preparation method and application thereof
By introducing nanoalumina into the positive electrode slurry and combining water as a solvent and conductive agent, the problem of insufficient stability and dispersion of the aqueous positive electrode slurry is solved, and the preparation of high-performance positive electrode slurry is achieved.
Patent Information
- Application Number
- CN202411545803.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing aqueous positive electrode slurry has problems such as poor stability, poor material dispersion and difficulty in coating films, which makes it difficult to explore homogenization processes.
By introducing nanoalumina into the positive electrode slurry, acting as a grinding medium, the dispersion of the slurry is improved, and water is used as a solvent, combining conductive agents and binders, a positive electrode slurry with good stability and dispersion is prepared.
The stability of the positive electrode slurry is improved, the dispersion performance of the material is improved, the homogenization process is simplified, and the production cost is reduced. It is suitable for the preparation of high-performance batteries.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and relates to a positive electrode slurry and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely accepted in many fields such as consumer electronics, transportation, power tools and energy storage. Phosphate-based cathode materials (e.g., lithium iron phosphate LiFePO4) have an olivine structure and are commonly used cathode materials in advanced lithium-ion batteries. Phosphate-based cathode material coatings have better safety, similar weight capacity, lower toxicity and moderate cost compared to lithiated transition metal layered oxides.
[0003] For the manufacture of electrodes, a process is usually used in which the electrode materials are dispersed in an aqueous or oily solvent for mixing. According to the type of solvent, which is an aqueous solvent (such as water) or an oily solvent (such as NMP), the process is divided into an aqueous process and an oily process. Among them, the aqueous process prepares an aqueous slurry, which has lower requirements for environmental temperature and humidity and can be used on a large scale. Moreover, compared with the oily process, the aqueous process has more advantages in safety and cost, so it is favored and has aroused great interest. However, there are several serious disadvantages of aqueous slurries: such as poor leveling control, stability of aqueous slurries, agglomeration of electrode material powders and carbon-based conductive additives, and difficulty in thin film coating, which make the exploration of homogenization processes more difficult.
[0004] Therefore, it is necessary to provide a strategy to improve the stability of electrode slurry, enhance the dispersion performance of materials in slurry, and reduce the agglomeration of materials, thereby facilitating the manufacture of electrodes and the preparation of high-performance batteries. Summary of the invention
[0005] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a positive electrode slurry and a preparation method and application thereof. The positive electrode slurry of the present invention has good stability and solves the problem of dispersibility of various materials in the positive electrode slurry.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a positive electrode slurry, which includes a phosphate-based positive electrode material, a conductive agent, a binder, nano-alumina and water.
[0008] In the present invention, nano alumina refers to alumina having a particle size in the range of 1 nm to 50 nm. For example, the particle size can be 1 nm, 2 nm, 3 nm, 5 nm, 6 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 19 nm, 20 nm, 22 nm, 23 nm, 24 nm, 26 nm, 28 nm, 30 nm, 33 nm, 36 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm or 50 nm, etc.
[0009] Conventional positive electrode slurry solvents generally use NMP, which is highly toxic and environmentally unfriendly, which is not conducive to the promotion and application of positive electrode slurry. The present invention uses water as a solvent to prepare an environmentally friendly positive electrode slurry. Furthermore, the present invention breaks through the problem that oily phosphate-based positive electrode materials are difficult to disperse in water, and improves the dispersibility of oily positive electrode particles in water by introducing nano-alumina. The technical principle is:
[0010] By introducing nano-alumina into the positive electrode slurry, it has excellent mechanical properties and can act as a grinding medium. In the process of preparing the positive electrode slurry, it can be equivalent to nano-scale zirconium beads to disperse the slurry, thereby improving the dispersibility of the slurry. The conductive agent in the positive electrode slurry can improve the conductivity of the slurry, thereby improving the electrochemical performance of the electrode prepared using the slurry. The following is a preferred technical solution of the present invention, but it is not a limitation to the technical solution provided by the present invention. Through the following preferred technical solution, the technical purpose and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, the nano-alumina is α-Al2O3. The α-Al2O3 material has a fine surface and a hard texture, and can be used in positive electrode slurry to effectively improve the dispersibility of the slurry.
[0012] Preferably, based on the total mass of the phosphate-based positive electrode material, the conductive agent and the nano-alumina as 100%, the content of the nano-alumina is 1%-10%, for example, it can be 1%, 2%, 3%, 3.5%, 4%, 5%, 6%, 7%, 7.5%, 8%, 9% or 10%, etc.
[0013] Preferably, the conductive agent comprises carbon nanotubes. Carbon nanotubes have excellent electrical conductivity, but are difficult to disperse due to their physical properties. By using them in combination with a dispersant, the problem of their dispersibility can be effectively solved, thereby making full use of their advantages of good electrical conductivity.
[0014] Preferably, based on the total mass of the phosphate-based positive electrode material, the conductive agent and nano-alumina as 100%, the content of the conductive agent is 5%-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0015] Preferably, based on the total mass of the phosphate-based positive electrode material, the conductive agent and nano-alumina as 100%, the content of the phosphate-based positive electrode material is 75%-94%, for example, it can be 75%, 76%, 78%, 80%, 82%, 83%, 85%, 88%, 90%, 92% or 94%, etc.
[0016] Preferably, the binder includes at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane.
[0017] Preferably, the positive electrode slurry further includes at least one of a dispersant and a wetting agent.
[0018] Preferably, the dispersant includes at least one of sodium dodecyl sulfate and zirconium oxide. Sodium dodecyl sulfate is a surfactant that can effectively reduce the surface tension of the conductive agent (such as carbon nanotubes) and improve the dispersibility of the carbon nanotubes. Zirconium oxide is an inorganic material that can form a composite material with the conductive agent (such as carbon nanotubes) to improve the dispersibility of the carbon nanotubes.
[0019] Preferably, the amount of the dispersant is 0.1%-0.5% of the total mass of the reaction system, for example, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc. The reaction system refers to the total mass of the liquid obtained after all the materials are added. Preferably, the wetting agent includes at least one of polyether siloxane, modified polyether siloxane and alcohol.
[0020] Preferably, the amount of the wetting agent is 5%-20% of the total mass of the reaction system, for example, 5%, 7%, 8%, 10%, 12%, 15%, 16%, 18% or 20%, etc. The reaction system refers to the total mass of the liquid obtained after all materials are added.
[0021] In a second aspect, the present invention provides a method for preparing the positive electrode slurry as described in the first aspect, the preparation method comprising the following steps:
[0022] The positive electrode slurry is obtained by mixing the phosphate positive electrode material, the conductive agent, the binder and the nano-alumina.
[0023] In the method of the present invention, during the high-speed stirring process, the nano-alumina acts as a grinding medium, which is equivalent to nano-scale zirconium beads, thereby facilitating the improvement of the dispersibility of the positive electrode slurry.
[0024] The method of the invention is simple, has low production cost and low maintenance cost, and is conducive to popularization and use.
[0025] Preferably, the phosphate-based cathode material is an unmodified phosphate-based cathode material and / or a semi-phase-change modified phosphate-based cathode material, wherein the semi-phase-change modified phosphate-based cathode material is prepared by the following method:
[0026] (a) subjecting an unmodified phosphate-based cathode material to a heat treatment under the protection of a protective gas;
[0027] (b) treating the material obtained in step (a) in water at a temperature not lower than 100° C. and drying the material to obtain a semi-phase-change modified phosphate-based positive electrode material.
[0028] By subjecting the phosphate-based cathode material to a semi-phase change modification, the single hydrogen-oxygen bonds on its surface are modified into hydrogen bonds. The hydrogen bonds are coated on the surface of the phosphate-based material (such as lithium iron phosphate) to increase its solubility in water, thereby improving the solubility between the material and the solvent, thereby improving the stability of the aqueous slurry.
[0029] In step (a) of the present invention, the type of protective gas is not specifically limited, including but not limited to at least one of nitrogen, helium and argon.
[0030] Preferably, the temperature of the heat treatment in step (a) is 650°C-750°C, for example, it can be 650°C, 660°C, 680°C, 700°C, 725°C, 730°C, 740°C or 750°C.
[0031] Preferably, the heat treatment time in step (a) is 4 h to 6 h, for example, 4 h, 4.5 h, 5 h, 5.5 h or 6 h.
[0032] Preferably, the water in step (b) is boiling water. By using boiling water as a solvent for treatment, the dispersibility of the positive electrode material in water can be further improved.
[0033] In one embodiment, the water temperature can be maintained and increased by increasing the ambient pressure.
[0034] Preferably, the treatment in step (b) is accompanied by ultrasound.
[0035] In one embodiment, the drying method of step (b) is vacuum drying, and the vacuum drying temperature is 50°C-70°C, for example, it can be 50°C, 52°C, 55°C, 58°C, 60°C, 65°C or 70°C; the vacuum drying time is 15h-22h, for example, it can be 15h, 16h, 18h, 19h, 20h, 21h or 22h.
[0036] As a preferred technical solution of the preparation method of the present invention, the phosphate-based positive electrode material is a powder. Before use, the powder is pre-mixed with lithium chloride hydrate and stirred to obtain a treated powder.
[0037] The adsorption force on the surface of small-particle phosphate-based positive electrode materials is much greater than their own electrostatic force, resulting in poor water solubility. This preferred technical solution pre-mixes and stirs them with lithium chloride hydrate. The stirred materials will attract each other due to the electric field force to form a material with a larger particle size, thereby using a simple physical method to improve the water solubility of the material in the aqueous slurry. Moreover, because lithium chloride hydrate contains crystal water, the mixed material contains crystal water, which reduces the surface energy of the material, increases hydrophilicity, and is easier to mix evenly with water later.
[0038] It should be noted that if the large-particle lithium iron phosphate material in the existing technology is directly used, although the solubility is increased, it will also cause the lithium ion deintercalation path inside the lithium iron phosphate particles to become longer during the battery charging and discharging process, which will have a negative impact on the rate performance of the lithium battery.
[0039] Preferably, based on the total mass of the powder and lithium chloride hydrate as 100%, the mass proportion of the lithium chloride hydrate is 5%-20%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 17%, 18% or 20%, etc. In one embodiment, the equipment used to mix the powder and lithium chloride hydrate is a planetary mixer.
[0040] Preferably, the method for preparing the positive electrode slurry comprises:
[0041] S1. Adding a conductive agent and a phosphate-based positive electrode material to a binder glue solution, dispersing them, and obtaining a first material;
[0042] S2 adds water to the first material to disperse it, thereby obtaining a second material;
[0043] S3 adds nano-alumina to the second material and disperses it to obtain a third material;
[0044] S4: adding a wetting agent to the third material, stirring and then sand-milling to obtain a positive electrode slurry.
[0045] Preferably, the adhesive solution in step S1 is obtained by mixing an adhesive with a solvent.
[0046] Preferably, the solid content of the adhesive solution in step S1 is 15%-30%, for example, it can be 15%, 16%, 18%, 20%, 22%, 23%, 24%, 25%, 26%, 28% or 30%.
[0047] Preferably, step S1 comprises: firstly adding a part of the conductive agent and a part of the phosphate-based positive electrode material to the binder glue, performing a first high-speed stirring, and then adding the remaining conductive agent and the phosphate-based positive electrode material to the obtained material, and performing a second high-speed stirring.
[0048] Preferably, the solid content of the adhesive glue is 15%-30%, for example, it can be 15%, 16%, 17%, 18%, 20%, 22%, 25% or 30%.
[0049] Preferably, the viscosity of the adhesive glue is 200mPa.s-1500mPa.s, for example, it can be 200mPa.s, 300mPa.s, 400mPa.s, 500mPa.s, 550mPa.s, 600mPa.s, 650mPa.s, 700mPa.s, 750mPa.s, 800mPa.s, 850mPa.s, 900mPa.s, 950mPa.s, 1000mPa.s, 1050mPa.s, 1100mPa.s, 1200mPa.s, 1300mPa.s, 1400mPa.s or 1500mPa.s, etc.
[0050] Preferably, the portion of the conductive agent accounts for 40%-60% of the total mass of the conductive agent, for example, it may be 40%, 42%, 44%, 45%, 48%, 50%, 55% or 60%, etc.
[0051] Preferably, the portion of phosphate-based positive electrode material accounts for 40%-60% of the total mass of the phosphate-based positive electrode material, for example, it may be 40%, 42%, 44%, 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.
[0052] Preferably, the rotation speed of the first high-speed stirring is 2000 r / min-2600 r / min, for example, it can be 2000 r / min, 2100 r / min, 2300 r / min, 2500 r / min or 2600 r / min.
[0053] Preferably, the first high-speed stirring time is 30 min-60 min, for example, it can be 30 min, 33 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0054] Preferably, the rotation speed of the second high-speed stirring is 2000 r / min-2600 r / min, for example, it can be 2000 r / min, 2100 r / min, 2300 r / min, 2500 r / min or 2600 r / min.
[0055] Preferably, the second high-speed stirring time is 60 min-90 min, for example, it can be 60 min, 65 min, 70 min, 75 min, 80 min, 85 min or 90 min.
[0056] Preferably, the dispersion speed in step S2 is 2000r / min-2600r / min, for example, it can be 2000r / min, 2100r / min, 2300r / min, 2500r / min or 2600r / min, etc.; the dispersion time in step S2 is 30min-45min, for example, it can be 30min, 32min, 35min, 37min, 40min or 45min, etc.
[0057] Preferably, the dispersion speed in step S3 is 2000 r / min-2600 r / min, for example, it can be 2000 r / min, 2100 r / min, 2300 r / min, 2500 r / min or 2600 r / min, etc.; the dispersion time in step S3 is 60 min-90 min, for example, it can be 60 min, 65 min, 70 min, 75 min, 80 min, 85 min or 90 min, etc.
[0058] Preferably, the stirring speed in step S4 is 10 r / min-15 r / min, for example, it can be 10 r / min, 11 r / min, 12 r / min, 13 r / min, 14 r / min or 15 r / min.
[0059] Preferably, the stirring time in step S4 is 30 min-45 min, for example, it can be 30 min, 33 min, 36 min, 40 min, 42 min or 45 min.
[0060] Preferably, the sanding in step S4 is performed 2 to 3 times.
[0061] Preferably, the parameters of the sanding in step S4 are: the sanding speed is 800r / min-1200r / min, for example, it can be 800r / min, 850r / min, 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min or 1200r / min, etc.; the sanding time is 5min-15min, for example, it can be 5min, 6min, 7min, 8min, 10min, 12min, 13min or 15min, etc.
[0062] In a third aspect, the present invention provides a positive electrode sheet, which is prepared using the positive electrode slurry described in the first aspect.
[0063] In a fourth aspect, the present invention provides a lithium battery, comprising the positive electrode sheet described in the third aspect.
[0064] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] (1) The present invention uses water as a solvent to prepare an environmentally friendly positive electrode slurry. Furthermore, the present invention overcomes the difficulty of oily phosphate-based positive electrode materials being difficult to disperse in water, and improves the dispersibility of oily positive electrode particles in water by introducing nano-alumina.
[0067] (2) The present invention modifies the phosphate-based positive electrode material by semi-phase change, so that the single hydrogen-oxygen bonds on its surface are modified into hydrogen bonds. The hydrogen bonds are coated on the surface of the phosphate-based material (such as lithium iron phosphate) to increase its solubility in water, improve the solubility between the material and the solvent, and thus improve the stability of the aqueous slurry.
[0068] (3) The present invention premixes lithium iron phosphate with lithium chloride hydrate and stirs them. The materials after stirring will attract each other due to the electric field force to form a material with a larger particle size, thereby improving the water solubility of the material in the aqueous slurry by a simple physical method. In addition, because lithium chloride hydrate contains crystal water, the mixed material contains crystal water, which reduces the surface energy of the material and increases its hydrophilicity, making it easier to mix evenly with water later.
[0069] (4) The method of the present invention is simple, has low production cost and low maintenance cost, and is conducive to popularization and use. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0071] The embodiments of the present invention are described in detail below so that the advantages and features of the invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0072] In the embodiments of the present invention, the purchase sources of various raw materials are as follows:
[0073] Carbon nanotubes were purchased from MacLean Group, G991390 carbon nanotubes.
[0074] The modified polyacrylic acid glue was purchased from Sinopharm Chemical Reagent Co., Ltd., with an average molecular weight of MW-5000, a solid content of 20%, and a viscosity of 1000 mPa·s.
[0075] Modified polyether siloxane can be purchased from Sinopharm Group with 99% purity and is produced by Beijing Wokai Biotechnology Co., Ltd.
[0076] The particle size distribution of the lithium iron phosphate powder used in the preparation method is: D50=1.34 μm, D90=3.63 μm, D97=8.25 μm.
[0077] Example 1
[0078] This embodiment provides a positive electrode slurry, including lithium iron phosphate, carbon nanotubes, modified polyacrylic acid, nano α-alumina, sodium dodecyl sulfate, modified polyether siloxane and water;
[0079] Wherein, taking the total mass of the lithium iron phosphate, carbon nanotubes and nano-α-alumina as 100%, the content of nano-α-alumina is 5%, the content of carbon nanotubes is 5%, and the content of lithium iron phosphate is 90%;
[0080] The solid mass of the modified polyacrylic acid accounts for 6% of the total mass of the positive electrode slurry;
[0081] The mass of sodium dodecyl sulfate accounts for 0.5% of the total mass of the positive electrode slurry;
[0082] The mass of the modified polyether siloxane accounts for 10% of the total mass of the positive electrode slurry.
[0083] This embodiment also provides a method for preparing the above-mentioned positive electrode slurry, comprising the following steps:
[0084] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 r / min for 30 min to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s);
[0085] S2 is the first dispersion, in which 50% of carbon nanotubes and 50% of lithium iron phosphate powder are added to the glue obtained in step S1, and the dispersion is carried out at a high speed of 2000 r / min for 30 minutes.
[0086] S3 is dispersed for the second time, and 50% of the carbon nanotubes and the remaining 50% of the lithium iron phosphate powder are continuously added, and dispersed at a high speed of 2600 r / min for 90 minutes to obtain the first material.
[0087] S4: adding water to the first material, and dispersing at a high speed of 2000 r / min for 30 min to obtain a second material;
[0088] S5: adding nano-α-alumina to the second material, and dispersing at a high speed of 2000 r / min for 90 min to obtain a third material;
[0089] S6: Add a wetting agent (modified polyether siloxane) to the third material. After adding, slowly stir at 15 r / min for 30 min, and then sand grind (speed is 1000 r / min, time is 10 min) to obtain a positive electrode slurry.
[0090] Example 2
[0091] The difference between this embodiment and embodiment 1 is that, taking the total mass of the lithium iron phosphate, carbon nanotubes and nano α-alumina as 100%, the content of nano α-alumina is 10%, the content of carbon nanotubes is 10%, and the content of lithium iron phosphate is 80%.
[0092] Example 3
[0093] This embodiment provides a positive electrode slurry, including lithium iron phosphate, carbon nanotubes, modified polyacrylic acid, nano α-alumina, sodium dodecyl sulfate, modified polyether siloxane and water;
[0094] Wherein, taking the total mass of the lithium iron phosphate, carbon nanotubes and nano-α-alumina as 100%, the content of nano-α-alumina is 8%, the content of carbon nanotubes is 6%, and the content of lithium iron phosphate is 86%;
[0095] The solid mass in the modified polyacrylic acid accounts for 5% of the total mass of the positive electrode slurry;
[0096] The mass of sodium dodecyl sulfate accounts for 0.3% of the total mass of the positive electrode slurry;
[0097] The mass of the modified polyether siloxane accounts for 10% of the total mass of the positive electrode slurry.
[0098] This embodiment also provides a method for preparing the above-mentioned positive electrode slurry, comprising the following steps:
[0099] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 r / min for 30 min to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s);
[0100] S2 is the first dispersion, in which 40% of carbon nanotubes and 50% of lithium iron phosphate powder are added to the glue obtained in step S1, and the mixture is dispersed at a high speed of 2000 r / min for 30 minutes.
[0101] S3 is a second dispersion, in which 60% of the carbon nanotubes and the remaining 50% of the lithium iron phosphate powder are continuously added, and the dispersion is performed at a high speed of 2600 r / min for 60 minutes to obtain the first material.
[0102] S4: adding water to the first material, and dispersing at a high speed of 2300 r / min for 40 min to obtain a second material;
[0103] S5: adding nano-α-alumina to the second material, and dispersing at a high speed of 2500 r / min for 70 min to obtain a third material;
[0104] S6: Add a wetting agent (modified polyether siloxane) to the third material. After adding, slowly stir at 10 r / min for 45 min, and then sand grind (speed is 800 r / min, time is 15 min) to obtain a positive electrode slurry.
[0105] Example 4
[0106] This embodiment provides a positive electrode slurry, including lithium iron phosphate, carbon nanotubes, modified polyacrylic acid, nano α-alumina, sodium dodecyl sulfate, modified polyether siloxane and water;
[0107] Wherein, taking the total mass of the lithium iron phosphate, carbon nanotubes and nano-α-alumina as 100%, the content of nano-α-alumina is 10%, the content of carbon nanotubes is 15%, and the content of lithium iron phosphate is 75%;
[0108] The solid mass in the modified polyacrylic acid accounts for 7% of the total mass of the positive electrode slurry;
[0109] The mass of sodium dodecyl sulfate accounts for 0.1% of the total mass of the positive electrode slurry;
[0110] The mass of the modified polyether siloxane accounts for 10% of the total mass of the positive electrode slurry.
[0111] This embodiment also provides a method for preparing the above-mentioned positive electrode slurry, comprising the following steps:
[0112] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 r / min for 30 min to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s);
[0113] S2 is the first dispersion, in which 50% of carbon nanotubes and 60% of lithium iron phosphate powder are added to the glue obtained in step S1, and the dispersion is carried out at a high speed of 2250 r / min for 45 minutes.
[0114] S3 is dispersed for the second time, and 50% of carbon nanotubes and the remaining 40% of lithium iron phosphate powder are continuously added, and dispersed at a high speed of 2400 r / min for 75 minutes to obtain the first material.
[0115] S4: adding water to the first material, and dispersing at a high speed of 2100 r / min for 45 min to obtain a second material;
[0116] S5: adding nano-α-alumina to the second material, and dispersing at a high speed of 2300 r / min for 80 min to obtain a third material;
[0117] S6: Add a wetting agent (modified polyether siloxane) to the third material. After adding, slowly stir at 15 r / min for 40 min, and then sand grind (speed is 1200 r / min, time is 5 min) to obtain a positive electrode slurry.
[0118] Example 5
[0119] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method, the lithium iron phosphate powder is replaced with treated lithium iron phosphate, wherein the treatment method is:
[0120] The lithium iron phosphate powder in Example 1 was mixed with lithium chloride hydrate in a mass ratio of 9:1, and stirred in a planetary mixer to obtain treated agglomerated lithium iron phosphate (D50=2.46 μm, D90=9.32 μm, D97=16.24 μm).
[0121] Example 6
[0122] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method, the lithium iron phosphate powder is replaced with pre-treated lithium iron phosphate, wherein the treatment method is:
[0123] The lithium iron phosphate powder in Example 1 was heat treated under nitrogen protection (temperature of 700° C., time of 5 h), then ultrasonicated in boiling water at 100° C., and vacuum dried at 50° C. for 22 h to obtain treated lithium iron phosphate.
[0124] Example 7
[0125] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method, the lithium iron phosphate powder is replaced with pre-treated lithium iron phosphate, wherein the treatment method is:
[0126] The lithium iron phosphate powder in Example 1 was heat treated under nitrogen protection (temperature of 750° C., time of 4 h), then ultrasonicated in boiling water at 100° C., and vacuum dried at 60° C. for 18 h to obtain treated lithium iron phosphate.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 1 is that, based on the total mass of the lithium iron phosphate, carbon nanotubes and nano α-alumina as 100%, the content of nano α-alumina is 0%, the content of carbon nanotubes is 5%, and the content of lithium iron phosphate is 95%.
[0129] Comparative Example 2
[0130] The difference between this comparative example and Example 1 is that, based on the total mass of the lithium iron phosphate, carbon nanotubes and nano α-alumina as 100%, the content of nano α-alumina is 10%, the content of carbon nanotubes is 0%, and the content of lithium iron phosphate is 90%.
[0131] Comparative Example 3
[0132] The difference between this comparative example and Example 1 is that, based on the total mass of the lithium iron phosphate, carbon nanotubes and nano α-alumina as 100%, the content of nano α-alumina is 0%, the content of carbon nanotubes is 0%, and the content of lithium iron phosphate is 100%.
[0133] Preparation of positive electrode:
[0134] The positive electrode slurries of Examples 1-7 and Comparative Examples 1-3 were coated on aluminum foil and baked at 120° C. for 20 minutes to obtain positive electrode sheets.
[0135] Performance test of the prepared positive electrode sheet:
[0136] (1) Coating resistance test: Cut the sample into pieces of 3 cm × 3 cm and test it with a pole piece resistance meter. Place the sample in the pole piece resistance meter and test it at a pressure of 60 MPa. Record the penetration resistance of the sample.
[0137] (2) Dyne value test: Use a dyne pen to test the dyne value. Take a 20cm×5cm sample and use a dyne pen with different parameters to draw on the sample. Observe the shrinkage of the ink of the dyne pen. If there is no change in the ink, it means that the parameters on the dyne pen correspond to the dyne value of the sample. If the ink shrinks, use a dyne pen with a smaller dyne value.
[0138] Dyne value is an index used to evaluate the coating performance of a fluid, especially used to evaluate the fluidity and stability of the fluid.
[0139] (3) Contact angle test: Cut the sample into 8 cm × 4 cm size and place it on the operating table of the surface tension meter. The surface tension meter drops water on the sample and measures the angle between the water drop and the sample surface through the observation mirror. This is the contact angle test.
[0140] See Table 1 for the results.
[0141] Table 1
[0142] serial number Coating resistance (mΩ) Dyne value Contact angle (°) Example 1 75 66 20.46 Example 2 105 64 28.56 Example 3 110 64 29.45 Example 4 109 64 29.14 Example 5 70 68 19.77 Example 6 73 67 20.01 Example 7 71 67 19.89 Comparative Example 1 128 54 54.78 Comparative Example 2 193 52 73.25 Comparative Example 3 226 50 79.25
[0143] It can be seen from Table 1 that the positive electrode slurry of the present invention has good conductivity, good dispersibility, good affinity with water, and the coating formed by the positive electrode slurry has good stability.
[0144] At the same time, by comparing Example 1 with Example 5, it can be seen that by pre-mixing and stirring the lithium iron phosphate powder with the lithium chloride hydrate, the stirred materials will attract each other due to the electric field force to form agglomerated lithium iron phosphate with a larger particle size, thereby improving the water solubility of the material in the aqueous slurry by a simple physical method. Moreover, because lithium chloride hydrate contains crystal water, the mixed material contains crystal water, which reduces the surface energy of the material, increases the hydrophilicity, and is easier to mix evenly with water later.
[0145] By comparing Example 1 with Examples 6-7, it can be seen that after the lithium iron phosphate active material is processed, the sample undergoes a phase change, the properties of the sample are changed, and the performance of the sample is affected.
[0146] By comparing Example 1 with Comparative Example 1, it can be seen that not adding α-Al2O3 will seriously affect the homogenization process, affect the uniformity of the slurry, cause uneven dispersion of the slurry, and affect the performance of the slurry.
[0147] By comparing Example 1 with Comparative Example 2, it can be seen that without adding carbon nanotubes, the conductive agent in the slurry is greatly reduced, which seriously affects the slurry performance.
[0148] By comparing Example 1 with Comparative Example 3, it can be seen that due to the lack of α-Al2O3 and carbon nanotubes, the dispersibility and conductivity of the slurry deteriorate, and the performance of the sample is poor.
[0149] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode slurry, characterized in that: The positive electrode slurry comprises a phosphate positive electrode material, a conductive agent, a binder, nano-alumina and water.
2. The positive electrode slurry according to claim 1, characterized in that The nano aluminum oxide is α-Al2O3; Preferably, based on the total mass of the phosphate-based positive electrode material, the conductive agent and the nano-alumina as 100%, the content of the nano-alumina is 1%-10%; Preferably, the conductive agent comprises carbon nanotubes; Preferably, based on the total mass of the phosphate-based positive electrode material, the conductive agent and the nano-alumina as 100%, the content of the conductive agent is 5%-15%; Preferably, based on the total mass of the phosphate positive electrode material, the conductive agent and the nano-alumina as 100%, the content of the phosphate positive electrode material is 75%-94%; Preferably, the binder comprises at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane; Preferably, the positive electrode slurry further includes at least one of a dispersant and a wetting agent; Preferably, the dispersant comprises at least one of sodium lauryl sulfate and zirconium oxide; Preferably, the amount of the dispersant is 0.1%-0.5% of the total mass of the reaction system; Preferably, the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohol; Preferably, the amount of the wetting agent is 5%-20% of the total mass of the reaction system.
3. A method for preparing a positive electrode slurry according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The positive electrode slurry is obtained by mixing the phosphate positive electrode material, the conductive agent, the binder and the nano-alumina.
4. The preparation method according to claim 3, characterized in that: The phosphate-based positive electrode material is an unmodified phosphate-based positive electrode material and / or a semi-phase-change modified phosphate-based positive electrode material, wherein the semi-phase-change modified phosphate-based positive electrode material is prepared by the following method: (a) subjecting an unmodified phosphate-based cathode material to a heat treatment under the protection of a protective gas; (b) treating the material obtained in step (a) in water at a temperature not lower than 100° C. and drying the material to obtain a semi-phase-change modified phosphate-based positive electrode material.
5. The preparation method according to claim 4, characterized in that: The temperature of the heat treatment in step (a) is 650°C-750°C; Preferably, the heat treatment time in step (a) is 4h-6h; Preferably, the water in step (b) is boiling water; Preferably, the treatment in step (b) is accompanied by ultrasound.
6. The preparation method according to claim 3, characterized in that: The phosphate-based positive electrode material is a powder. Before use, the powder is mixed with lithium chloride hydrate and stirred to obtain a treated powder.
7. The preparation method according to claim 3, characterized in that: The preparation method of the positive electrode slurry comprises: S1. Adding a conductive agent and a phosphate-based positive electrode material to a binder glue solution, dispersing them, and obtaining a first material; S2 adds water to the first material to disperse it, thereby obtaining a second material; S3 adds nano-alumina to the second material and disperses it to obtain a third material; S4: adding a wetting agent to the third material, stirring and then sand-milling to obtain a positive electrode slurry.
8. The preparation method according to claim 7, characterized in that: Step S1: the adhesive glue is obtained by mixing the adhesive and the solvent; Preferably, the solid content of the adhesive solution in step S1 is 15%-30%; Preferably, step S1 comprises: firstly adding a part of the conductive agent and a part of the phosphate-based positive electrode material to the binder glue, performing a first high-speed stirring, and then adding the remaining conductive agent and the phosphate-based positive electrode material to the obtained material, and performing a second high-speed stirring; Preferably, the solid content of the adhesive glue is 15%-30%; Preferably, the viscosity of the adhesive glue is 200mPa.s-1500mPa.s; Preferably, the portion of the conductive agent accounts for 40%-60% of the total mass of the conductive agent; Preferably, the portion of the phosphate-based cathode material accounts for 40%-60% of the total mass of the phosphate-based cathode material; Preferably, the rotation speed of the first high-speed stirring is 2000r / min-2600r / min; Preferably, the first high-speed stirring time is 30min-60min; Preferably, the rotation speed of the second high-speed stirring is 2000r / min-2600r / min; Preferably, the second high-speed stirring time is 60min-90min; Preferably, the dispersion speed in step S2 is 2000r / min-2600r / min, and the dispersion time in step S2 is 30min-45min; Preferably, the dispersion speed in step S3 is 2000r / min-2600r / min, and the dispersion time in step S3 is 60min-90min; Preferably, the stirring speed in step S4 is 10r / min-15r / min; Preferably, the stirring time in step S4 is 30 min-45 min; Preferably, the number of sanding in step S4 is 2 to 3 times; Preferably, the parameters of the sanding in step S4 are: the sanding speed is 800r / min-1200r / min, and the sanding time is 5min-15min.
9. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared using the positive electrode slurry described in claim 1 or 2.
10. A lithium battery, characterized in that: The lithium battery comprises the positive electrode sheet according to claim 9.
Citation Information
Cited By
Positive electrode mixing method of lithium-manganese primary battery, prepared positive electrode mixture and application of positive electrode mixture
CN121565783A